FROM AUTOIMMUNITY TO INNOVATION: A NARRATIVE REVIEW OF VITILIGO AND ITS MANAGEMENT - Katarzyna Malinowska; Elhatra Settaf-Cherif; Joanna Barwacz; Magdalena Adamik; Layla Settaf-Cherif; Marta Czarnowska; Radosław Sciepuro; Mateusz Malinowski; Dagmara Gładysz (International Journal of Innovative Technologies in Social Science, 2025)
Background: Vitiligo is a chronic skin disorder characterized by the development of hypopigmented or depigmented macules and patches, resulting from the loss of functional melanocytes in the affected areas. It is estimated to affect approximately 0.5% to 4% of the global population. Although the exact etiology remains unclear, vitiligo is considered an acquired, multifactorial condition involving complex interactions. Aim: To summarize current knowledge on vitiligo, focusing on its pathogenesis, clinical presentation, diagnostic principles, and therapeutic strategies. Methodology: Literature review was conducted using PubMed, the Cochrane Library, and Google Scholar databases. Results: Vitiligo is now widely regarded as an autoimmune disorder. Current management centers on immune modulation through topical and systemic agents, phototherapy, and, in selected cases, surgical intervention. Adjunctive measures including camouflage techniques, nutritional optimization, and psychological support play an important role in improving quality of life. Conclusions: Vitiligo results from complex autoimmune and oxidative processes leading to melanocyte destruction. First-line treatment typically includes topical corticosteroids or calcineurin inhibitors, with phototherapy serving as an effective and well-established adjunct. Combination and targeted immunomodulatory therapies, such as JAK inhibitors, represent promising future directions. Despite notable advances, complete and durable repigmentation remains uncommon, highlighting the need for continued research and individualized patient care.